Consensus on scales for an interdisciplinary health assessment tool for the elderly population - Maria Clara Duarte Monteiro; Maria Manuela Ferreira Pereira da Silva Martins; Soraia Dornelles Schoeller (Rev Rene, 2022)
Objective: to describe the consensus of the content of an instrument for assessing interdisciplinary health care of the elderly population. Methods: consensus study conducted among physicians, nurses, and social workers, contemplating the construction of instrument and the pre-test for selection of scales for use in practice. Questionnaire consisting of questions that identified representative scales in the assessment of the elderly. The scales that obtained consensus criterion of equal to or greater than 75% were considered selected by the experts. Sample was composed through snowball sampling, resulting in 101 participants. Results: of the 13 scales submitted,the professionals indicated that eight were suitable for use and two were already applied within their practice. The excluded became part of the recommendations for good practices in elderly care. A discrepancy was identified between what they consider to be useful and of interest versus what is applied in practice. Conclusion: consensus among experts allowed us to identify and select interdisciplinary assessment data for a proposed instrument to support the care process. Contributions to practice: this contributes to awareness about the use of recommended scales for the elderly and to avoid the overlapping of the same interventions by several professionals, with significant gains for this population.